UPAYA PENYEDIAAN INFORMASI MELALUI PENYUSUNAN DATA PRODUK PERTUNJUKAN - Luh Komang Merawati; Kadek Anantazikha (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Ngurah Rai, 2020)
Bali Nusa Dua Theatre is an international theatre, classy and prestigious entertainment venue. The activities carried out by the company are doing an art performance with spectacular show that combines stage art, visual effects and sound systems, as well as dancers with various stage skills that are staged in the Bali Nusa Dua Theatre 4 times a week every Monday, Wednesday, Friday, and Saturday. The service program was carry out through the compilation of a data product performance. The method used in the activities of compiling the product data in Bali Nusa Dua Theatre is by conducting assistance and socialization. Compilation of product data in Bali Nusa Dua Theatre has been successfully carried out through assistance in compiling a product data by recording the types of product, names of dancers and dance studios of dancer.